Planejamento de produto industrial: o papel do marketing na doutrinação da filosofia ambiental. - Berra, Lizete (2003)
This work presents a proposal for the industrial product planning guided by an environmental managerial philosophy. It’s divided in four parts, beginning for verifying, in the chapter 1, the different focuses of the cycles; the pioneers of the ecological movement; the historical cycle of the ambiental administration of the industry Klabin Celulose Riocell. In Chapter 2 the focuses of the product are worked; the region of the Taquari’s Valley; batteries; the classification of the generators related to the type; project and design for the environment and the marketing. The data collected it is presented in the Chapter 3, about destination of solid residues, incompatibility of the Resolution in the 257/99 with the Law in the 6.938/81 of the poluter payer's principle, the process of batteries of the Lajeado’s district; the sanitary embankment of domestic residues and the industrial residues for, in Chapter 4, to contribute for the project of the industrial product - area of the author's concentration - with technology environmentally guided and, still, suggestions for future investigations about the theme. In the Final Considerations it was made a general analysis of the exposed theme, as well as they were made suggestions for future investigations.